S120 Adherence and quality of home-based spirometry in patients with ILD using a digital health platform during a 6-month period: data from the RALPMH study. (11th November 2022) - Althobiani, MA; Ranjan, Y; Jacob, J; Orini, M; Dobson, R; Porter, JC; Hurst, JJ; Folarin, A
Abstract : Introduction: Daily home-based spirometry has been suggested as a solution to detect lung function decline and disease progression in patients with ILD. However, quality and adherence of spirometry testing remain essential for successful adaptation in research and clinical practice. Aim: This study reports on adherence and unsupervised test quality using a real-time monitoring approach over six months. Methods: This data is from the prospective cohort study - Remote Assessment of Lung Disease and Impact on Physical and Mental Health (RALPMH). Patients received a package that includes a NuvoAir Air Next, Bluetooth wireless handheld spirometry. Patients were requested to download the NuvoAir mobile application and received virtual and/or face-to-face training to perform spirometry. Patients recorded up to three unsupervised tests daily for up to 183 days. They received a daily reminder via the RADAR questionnaire app to perform spirometry. Results: Twenty patients with ILD were recruited for the study (mean age and standard deviation 60.9±11.7 years. Of those, 11 (55%) were females. Patients recorded three unsupervised spirometry tests over up to 183 days. Adherence was defined by the number of home-based tests divided by the number of days enrolled in the study. Adherence to spirometry at least once a week was 94%, two tests a week 87%, and three sessions a week 80%. Adherence to at least one daily test session was 60% ( figure 1 ). In total, patients performed (2332; 64%) of the overall unsupervised sessions requested, 2154(92%) were of acceptable quality according to ATS grading: the majority were grade A (461; 20%) and B (1196; 51%). Other grades were C (88; 4%), D (55; 2%) and E (354; 15%). Only 178 (8%) were unacceptable ( figure 1 ). Conclusion: This study confirms the high quality and adherence to the use of unsupervised home-based spirometry in patients with ILD. These findings highlight the need for further research on home-based spirometry to assess whether this tool provides a meaningful assessment to detect lung function decline and progression in patients with ILD.